Conceptual Framework of an Information for Emergency Management for Higher Education in Thai Supply Chain - Chansamut, Artaphon (ExcelingTech, 2023)
The objective of research were to develop conceptual framework of an information for emergency management for higher education in Thai supply chain and to evaluate conceptual framework of an information for emergency management for higher education in Thai supply chain. The research sample totalling ten experts consisted of five experts on supply chain , five experts on information system. All of expert must have educational qualification at the doctoral degree level, and must have more than more than four years of work experience The research tool was questionnaire assessing the suitability about conceptual framework of an information for emergency management for higher education in Thai supply chain comprises five elements namely main components suppliers, University, Good service and security, Customers. The data analysed by using arithmetic mean and standard deviation. The assessment about conceptual framework of an information for emergency management for higher education in Thai supply chain using Black-Box technique. The overall model evaluation result was validated at a “Good” level, suggesting that conceptual framework of an information for emergency management for higher education in Thai supply chain aims to support sustainable information system development.